Activating effect of nasal air flow on epileptic electrographic abnormalities in the human EEG. Evidence for the reflect origin of the phenomenon - Kristof, M; Servít, Z; Manas, K (Physiologia Bohemoslovaca, 1981)
Deep nasal breathing [with the mouth closed] activates [to a certain extent selectively], in the human EEG, epileptic abnormalities of diencephalotemporal origin [Servít et al. 1977]. This activating effect could be suppressed by local anaesthesia of the mucosa membrane in the superior nasal meatus. The same abnormalities could be elicited or activated by air insufflation into the upper nasal cavity, without pulmonary hyperventilation. These results speak in favour of the assumption that a neural [reflex] mechanism of the activating effect of nasal hyperventilation is involved, with a reflexogenic area in the superior nasal meatus.
Keywords: Epilepsy; plicní ventilace; Electroencephalography; Pulmonary Ventilation; Reflex; epilepsie; nosní sliznice; lokální anestezie; Humans; Nasal Mucosa; Hyperventilation; reflex; lidé; elektroencefalografie; hyperventilace; Anesthesia, Local